Hematological indices and cognitive function in adolescent girls with iron-deficiency anemia: a systematic review - Nabila Sinta Devi; Rafi Andyah Arum Kedaton; Diadjeng Setya Wardani; Sri Andarini (Poltekkes Kemenkes Bandung, 2026)
Background: Iron deficiency anemia remains a global health problem, especially among adolescent girls, and may affect cognitive function. However, studies that specifically examine the link between hematological biomarkers and cognitive function in this group are still limited. Objective: This study aimed to examine the association between iron status and cognitive function in adolescent girls with iron-deficiency anemia. Methods: This study used a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines. Articles were searched in PubMed and Scopus from 2016 to 2025. Included studies were randomized controlled trials and intervention studies involving adolescent girls aged 10–19 years that reported hemoglobin (Hb), serum ferritin (sFt), total body iron (TBI), and cognitive function. Results: Improvements in iron status were generally associated with better cognitive function, especially in attention and memory. Interventions such as those particularly through biofortification and nutrition-based interventions. Conclusion: Improving iron status may help enhance cognitive function in adolescent girls. These findings highlight the importance of nutrition interventions, particularly in school settings.